EXPERIMENTAL ANALYSIS AND KINETIC MODELLING FOR STEAM GASIFICATION OF THE TURKISH LIGNITES - Guney, O. F.; Koyun, A. (YILDIZ TECHNICAL UNIV, 2020)
During the last decades, the importance of structural parameters has been increased because the models which have been developed using structural parameter can define the gasification process effectively. In this study, structural parameters, rates of conversion and activation energies of Zonguldak coal and Beypazari lignite have obtained. The samples of Zonguldak coal and Beypazari lignite used in this study have different characteristics. Pore dimensions, distribution of pores and surface areas were used as structural parameters. Suitable kinetic parameters were determined by fitting the gasification model to experimental data. The random pore model was used to define these kinetic parameters. The data were taken from experiments of Balci and Dumsoy and the results obtained from Zonguldak coal and Beypazan lignite pyrolysed in a vertical tube heated from outside by an inert gas and gasified with steam at elevated temperatures (between 700 degrees C and 1000 degrees C) were used in the model.
Keywords: Random Pore Model; Coal Gasification; Elevated Temperature; Porosity; FLUID-SOLID REACTIONS; COAL-CHAR; CO2 GASIFICATION; REACTIVITY; PYROLYSIS; Thermodynamics